2019
DOI: 10.1016/j.chiabu.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Child protection reports and removals of infants diagnosed with prenatal substance exposure

Abstract: Background: A frequent response for prenatal substance exposure (PSE) is intervention by child protective services (CPS). Previous research has examined differences in reports to CPS regarding PSE by substance exposure and by maternal race. However, little is known regarding the frequency of immediate removals by CPS relating to PSE and maternal race. Methods:We investigated hospital reports to CPS and CPS removals of PSE infants by using linked birth, hospital discharge, and CPS records for all children born … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 24 publications
2
33
1
Order By: Relevance
“…Among infants with prenatal opioid exposure, 11 percent were reported and removed by CWS authorities, compared with 30 percent for cocaine-exposed infants. While rates of reporting and removal were found to differ by the type of drug the infant was exposed to, this study found no differences based on race alone (Rebbe et al 2019). A systematic review of the research on maternal substance use and factors associated with child custody loss found cocaine use more commonly predicted custody loss than other types of drug use (Canfield et al 2017), but did not control for race.…”
Section: Investigating the Role Of Race Drug Type And Povertycontrasting
confidence: 69%
See 1 more Smart Citation
“…Among infants with prenatal opioid exposure, 11 percent were reported and removed by CWS authorities, compared with 30 percent for cocaine-exposed infants. While rates of reporting and removal were found to differ by the type of drug the infant was exposed to, this study found no differences based on race alone (Rebbe et al 2019). A systematic review of the research on maternal substance use and factors associated with child custody loss found cocaine use more commonly predicted custody loss than other types of drug use (Canfield et al 2017), but did not control for race.…”
Section: Investigating the Role Of Race Drug Type And Povertycontrasting
confidence: 69%
“…Some of these differences continue to be reflected in other ways, such as socioeconomic status. For example, amphetamine exposed infants also have a higher likelihood of reporting and/or removal (Putnam-Hornstein, Prindle, and Leventhal 2016; Rebbe et al 2019) and amphetamine use may be more common among minorities (specifically Hispanics) and/or low-socioeconomic status whites (Wermuth 2000;Wu et al 2009). While a focus on race alone does not account for the complexity of disparities within the CWS, there is ample evidence that it plays a critical role.…”
Section: Investigating the Role Of Race Drug Type And Povertymentioning
confidence: 99%
“…Previous research using the same dataset in Washington state found that only 13.3% of infants diagnosed with prenatal substance exposure were removed by CPS from their families during the neonatal period. 46 However, some states have taken more punitive approaches to diagnosed prenatal substance exposure, including the passage of legislation to prosecute mothers who use illicit drugs during pregnancy. 44 Such punitive actions may influence medical providers' decisions to report prenatal substance exposure infants to CPS.…”
Section: Discussionmentioning
confidence: 99%
“…As described in Mitchell and Petray (2016), these are both practical and "symbolic" policies, enacted to uphold some "dimension of morality" (e.g., equal access to marriage), rather than influence the day-to-day lives of most citizens (p. 288). Although we report that up to 15% of infants are born substance-exposed, the rate of diagnosis is much lower (Rebbe et al, 2019a), and the overall rate of infants who come to the attention of the child welfare system is also relatively low (Rebbe et al, 2019b). Nonetheless, protecting infants with PSE is an issue of great societal importance and concern (Graham, 2019).…”
Section: Diffusion Of Innovations (Doi) Theorymentioning
confidence: 93%